Local anesthetics elicit immune-dependent anticancer effects. Issue 4 (28th April 2022) - Bezu, Lucillia; Wu Chuang, Alejandra; Sauvat, Allan; Humeau, Juliette; Xie, Wei; Cerrato, Giulia; Liu, Peng; Zhao, Liwei; Zhang, Shuai; Le Naour, Julie; Pol, Jonathan; van Endert, Peter; et al.
Abstract : Background: Retrospective clinical trials reported a reduced local relapse rate, as well as improved overall survival after injection of local anesthetics during cancer surgery. Here, we investigated the anticancer effects of six local anesthetics used in clinical practice. Results: In vitro, local anesthetics induced signs of cancer cell stress including inhibition of oxidative phosphorylation, and induction of autophagy as well as endoplasmic reticulum (ER) stress characterized by the splicing of X-box binding protein 1 (XBP1s) mRNA, cleavage of activating transcription factor 6 (ATF6), phosphorylation of eIF2α and subsequent upregulation of activating transcription factor 4 (ATF4). Both eIF2α phosphorylation and autophagy required the ER stress-relevant eukaryotic translation initiation factor 2 alpha kinase 3 (EIF2AK3, best known as PERK). Local anesthetics also activated two hallmarks of immunogenic cell death, namely, the release of ATP and high-mobility group box 1 protein (HMGB1), yet failed to cause the translocation of calreticulin (CALR) from the ER to the plasma membrane. In vivo, locally injected anesthetics decreased tumor growth and improved survival in several models of tumors established in immunocompetent mice. Systemic immunotherapy with PD-1 blockade or intratumoral injection of recombinant CALR protein, increased the antitumor effects of local anesthetics. Local anesthetics failed to induce antitumor effects in immunodeficient mice or against cancers unable to activate ER stress or autophagy due to the knockout of EIF2AK3/PERK or ATG5, respectively. Uncoupling agents that inhibit oxidative phosphorylation and induce autophagy and ER stress mimicked the immune-dependent antitumor effects of local anesthetics. Conclusion: Altogether, these results indicate that local anesthetics induce a therapeutically relevant pattern of immunogenic stress responses in cancer cells.